Stoczniowcy opanujemy budowę nowoczesnych jednostek pełnomorskich (Gdańsk : [s.n.], 1951)
Plakat propagandowy.
Keywords: Stocznie -- Polska -- 1945-1970 -- plakaty; Stocznie -- Polska -- Gdańsk -- 1945-1970 -- plakaty